Spiro-OMeTAD or CuSCN as a preferable hole transport material for carbon-based planar perovskite solar cells. Issue 25 (19th June 2020) - Yang, Yang; Hoang, Minh Tam; Yao, Disheng; Pham, Ngoc Duy; Tiong, Vincent Tiing; Wang, Xiaoxiang; Wang, Hongxia
Abstract : Carbon electrode-based planar PSCs demonstrated higher device performance and reduced hysteresis using a CuSCN based HTL owing to its favourable energy level alignment with the perovskite compared to conventional spiro-OMeTAD based HTL. Abstract : A hole transport layer (HTL) plays the role of extracting hole carriers while improving interfacial contacts of perovskite/carbon in planar heterojunction perovskite solar cells using carbon based electrodes (C-PSCs). For the future application of C-PSCs, the HTL also needs to have good stability and easy processability while maintaining high device efficiency. Herein, we compare the behaviour of the most widely used HTL based on spiro-OMeTAD to the much less studied HTL based on CuSCN in planar C-PSCs. The results show that 14.7% power conversion efficiency (PCE) is obtained for CuSCN based C-PSCs with good reproducibility and negligible hysteresis behaviour. In contrast, the C-PSCs using spiro-OMeTAD show a much lower PCE (12.4%) and significant hysteresis phenomenon. We conduct systematic characterisation of the electronic and energetic properties of the C-PSCs to understand this phenomenon. We find that a more favourable energy level alignment of CuSCN with the perovskite than spiro-OMeTAD leads to a reduced charge injection barrier, which favours a more efficient hole extraction capability, inhibited carrier recombination and reduced ionic capacitance. This in turn leads to better PCE and lower hysteresis for the C-PSCs. Moreover, the CuSCN based C-PSCs also demonstrate better stability against moisture with a high PCE retention ratio of 93% under a humid environment (55–70%) for 80 days without encapsulation.